Intake Manifold Boosting of Turbocharged Spark-Ignited Engines - Lino Guzzella; Christopher Onder; Christoph Voser; Norbert Zsiga (Energies, 2013)
Downsizing and turbocharging is a widely used approach to reduce the fuel consumption of spark ignited engines while retaining the maximum power output. However, a substantial loss in drivability must be expected due to the occurrence of the so-called turbo lag. The turbo lag results from the additional inertia that the turbocharger adds to the system. Supplying air by an additional valve, the boost valve, to the intake manifold can be used to overcome the turbo lag. This turbo lag compensationmethod is referred to as intakemanifold boosting. The aims of this study are to show the effectiveness of intake manifold boosting on a turbocharged spark-ignited engine and to show that intake manifold boosting can be used as an enabler of strong downsizing. Guidelines for the dimensioning of the boost valve are given and a control strategy is presented. The trade-off between additional fuel consumption and the consumption of pressurized air during the turbo lag compensation is discussed. For a load step at 2000 rpm the rise time can be reduced from 2.8 s to 124ms, requiring 11.8 g of pressurized air. The transient performance is verified experimentally by means of load steps at various engine speeds to various engine loads.